Evaluasi Aktivitas Pemberantasan Sarang Nyamuk Melalui Gerakan 3M Plus dan G1R1J di Penjaringan, Jakarta Utara - Ali, Soegianto; Kaisar, Maria Mardalena Martini; Hengestu, Anastasia; Kristin, Helen; Anggraini, Felicia; Khustiawan, Sesilia Olivia Rachael (Institute for Research and Community Services, 2024)
Dengue infection, transmitted by Aedes spp. mosquitoes, is an endemic disease that burdens Indonesia. Aedes spp. mosquitoes and larvae density are correlated with the presence of unmanaged water storage containers. One of the efforts to reduce Dengue infections is the eradication of mosquito nests (Pemberantasan Sarang Nyamuk/PSN) at the community level through 3M Plus and one house one larval surveyor movement (Gerakan 1 Rumah 1 Jumantik/G1R1J). A community service in RW 08 and RW 15 Penjaringan Sub-district, done by the School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, aimed to re-evaluate the effectiveness of the 3M Plus and G1R1J activities that are routinely conducted in both areas using the larval counting result as indicators. Health cadres from both RWs routinely urge the residents to implement the PSN program. At the same time, the residents also implement the movements positively. Although in general, the program is being well implemented, during this activity, we still found larvae in 7.20% of water containers of some houses, thus suggesting that continuing both communication and education on 3M plus and G1RIJ is still needed.